ANTESENDEN TRUST PADA SHIPPING INDUSTRY DI INDONESIA - Sutoha Sutoha; Asep Suparman; Sarfilianty Anggiani (Universitas Trisakti, 2021)
Purpose - The purpose of this study was to analyze the influence of leadership (leading organizational and leading people) on terust trust and its impact on organizational performance Design/Methodology/Approach –The research design used is correlational research which aims to test and analyze the effect of the independent variable on the dependent variable. The variables used consist of leadership which consists of leading organizational and leading people, trust and organizational performance. The data used are primary data through a questionnaire distributed via google form. The number of respondents used was 195 respondents where the sampling method used purposive sampling. The analysis tool used is the Structural Equation Model (SEM) using AMOS 23 software.Finding – The results showed that leadership consisting of leading organizations and leading people had a positive effect on trust, while trsut million was proven to have a significant positive effect on organizational performance.Value / Implication - The results of the study have managerial implications for decision makers in companies that leadership, especially the leader's ability to leading employees, must receive a larger portion compared to the ability to leading the organization as an effort to improve organizational l performance.